Using English Comic Media to Improve English Reading Comprehension Ability in Viii Grade Students of SMP N 1 Modoinding - Karundeng, Pricillia Margaretha; Rombepajung, Paula A.; Wongkar, Yapi (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
Reading comprehension is one of the most important skills in learning English. In the process of learning English, the ability to read comprehension is an important variable that influences the achievement of learning outcomes according to the KKM in English lessons at SMP/MTs. One of the efforts to overcome students' difficulties in reading comprehension of English is the use of learning media. The researcher is interested in conducting a study entitled "Using English comic media to improve English reading comprehension ability in VIII grade students of SMP N 1 Modoinding. With this research design the researcher wants to know students' development of reading comprehension and Effect of English comic as a media to improve students’ ability skill to reading comprehension. The research that has been conducted aims to find out whether there is a significant influence or improvement from the using of comics on students' reading comprehension abilities. The results of this study also showed that the post-test scores were higher than the student scores in the pre-test.